2009
DOI: 10.1051/0004-6361/200811513
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur in the globular clusters 47 Tucanae and NGC 6752

Abstract: Context. The light elements Li, O, Na, Al, and Mg are known to show star-to-star variations in the globular clusters 47 Tuc and NGC 6752. Such variations are interpreted as coming from processing in a previous generation of stars. Aims. In this paper we investigate the abundances of the α-element sulfur, for which no previous measurements exist. In fact this element has not been investigated in any Galactic globular cluster so far. The only globular cluster for which such measurements are available is Terzan 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 52 publications
9
29
0
Order By: Relevance
“…Caffau et al (2005b) determined mean S abundance in Ter 7 to be slightly lower (by ∼0.1 dex) than in Galactic stars at similar metallicity. Sbordone et al (2009) analysed nine stars in the GC 47 Tuc ([Fe/H] = −0.72 dex) and four stars in NGC 6752 ([Fe/H] = −1.54 dex), deriving [S/Fe] = 0.18±0.14 and [S/Fe] = 0.49 ± 0.15 dex for the two GCs, respectively, which is consistent with the results of field stars. Curiously, Sbordone et al (2009) reported a star-to-star variation in the observed [S/Fe] ratio in 47 Tuc, which, although not significant with respect to the large measurement uncertainties, showed a strikingly clear correlation with the Na abundance.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Caffau et al (2005b) determined mean S abundance in Ter 7 to be slightly lower (by ∼0.1 dex) than in Galactic stars at similar metallicity. Sbordone et al (2009) analysed nine stars in the GC 47 Tuc ([Fe/H] = −0.72 dex) and four stars in NGC 6752 ([Fe/H] = −1.54 dex), deriving [S/Fe] = 0.18±0.14 and [S/Fe] = 0.49 ± 0.15 dex for the two GCs, respectively, which is consistent with the results of field stars. Curiously, Sbordone et al (2009) reported a star-to-star variation in the observed [S/Fe] ratio in 47 Tuc, which, although not significant with respect to the large measurement uncertainties, showed a strikingly clear correlation with the Na abundance.…”
Section: Introductionsupporting
confidence: 80%
“…Sbordone et al (2009) analysed nine stars in the GC 47 Tuc ([Fe/H] = −0.72 dex) and four stars in NGC 6752 ([Fe/H] = −1.54 dex), deriving [S/Fe] = 0.18±0.14 and [S/Fe] = 0.49 ± 0.15 dex for the two GCs, respectively, which is consistent with the results of field stars. Curiously, Sbordone et al (2009) reported a star-to-star variation in the observed [S/Fe] ratio in 47 Tuc, which, although not significant with respect to the large measurement uncertainties, showed a strikingly clear correlation with the Na abundance. The authors considered different possibilities for the occurrence of this correlation, including that S may be involved in the self-enrichment processes of GCs through the 31 P(p, γ) 32 S proton capture reaction.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…A result concerning P evolution that we find intriguing, is that of Sbordone et al (2009), who found that the sulphur A&A 532, A98 (2011) abundance in the globular cluster 47 Tuc displays a significant correlation with the Na abundance. The authors point out that S could be produced through proton capture reactions on P ( 31 P (p, γ) 32 S).…”
Section: Introductionsupporting
confidence: 55%
“…The recognition of this fact came with the increasing observational evidence for what was called "star-to-star abundance variations" or "abundance anomalies", which manifest themselves as variations of nitrogen, oxygen, and sodium, and in some clusters of magnesium and aluminum abundances. Lithium has been found to vary in a few cases (NGC 6752, NGC 6397, and 47 Tucanae, Pasquini et al 2005;Bonifacio et al 2007;Lind et al 2009;Shen et al 2010), anticorrelating with sodium, and hints exist that elements as heavy as sulfur might be affected (in 47 Tuc, Sbordone et al 2009). These abundance variations are found in stars of all evolutionary stages.…”
Section: Introductionmentioning
confidence: 99%